Efeito de níveis de fósforo não-fítico e de fitase sobre a tíbia de frangos de corte - Oliveira, M. C.; Silva, D.; Loch, F. C.; Laurentiz, A. C. [UNESP]; Junqueira, O. M. [UNESP] (My University, 2009)
It was evaluated the effect of nonphytate phosphorus (NNP) and phytase on broiler tibia. One thousand and two hundred chicks were allocated in a completely randomized design and factorial arrangement 4 x 3 (NPP x phytase levels), with four replicates. NPP levels, at each phase, were 0.45, 0.37, 0.29 and 0.21% - initial, 0.41, 0.33, 0.25 and 0.17% - growth, and 0.37, 0.29, 0.21 and 0.13% - withdrawal. Phytase levels were 0, 500 and 1000 FTU/kg of diet. There was no effect on diameter at 21 days of age. Tibia with lower weight, length and diaphysis, distal epiphysis and average densities e proximal epiphysis density resulted from NPP reduction from 0.37 to 0.29% and from 0.29 to 0.21%, respectively. Inclusion of 500 FTU/kg of phytase improved length and diaphysis density of the tibia, independent of NPP levels. Diets with NPP, at initial, growth and final phases, of 0.37, 0.33 and 0.29%, respectively, supplemented with 1000 FTU/kg of phytase, can be used with no negative effect on bone quality in broilers.
Effect of nonphytate phosphorus and phytase levels on broiler tibia
Keywords: Additives; Bone quality; Enzymes